Investigating the Vital Effects of Chemical Elements and Carbamide in Vegetable Green Cover - Aziz, Abdul Mohammad; Ziarmal, Zabihullah (Journal of Natural Sciences – Kabul University, 2024)
The green and beautiful cover of plants in nature holds significant importance. This article examines vegetation cover, the essential nutrients for plants, the elements that play a vital role in plant growth, and their chemical compound sources. The primary objective is to study the elements crucial for plant metabolism and external requirements, without which plants cannot complete their normal life cycle. These elements include nitrogen, phosphorus, potassium, calcium, sulfur, magnesium, carbon, oxygen, and hydrogen. Nitrogen, a vital plant element, is most abundantly found in the compound urea or carbamide (chemical formula CO(NH2)2). This white, odorless solid is highly soluble in water and serves as a nitrogen source for plants. This paper provides a detailed study of urea's role in plant nutrition.